Socioeconomic inequalities of childhood obesity in South Africa - Nakimuli, Brenda (Health Economics Unit, 2017)
Obesity is a public health concern in both high- and low-middle income countries. In South Africa obesity is not only limited to adults but is also evidenced in children. In order to contribute useful insights for developing effective obesity policy and programme interventions, this study assesses socioeconomic (SE) inequalities related to childhood obesity in South Africa. Using data from the South African National Income Dynamics survey (2012), the study assesses the extent of SE inequalities in obesity using concentration index (CI). The study also assesses the determinants that underpin these inequalities using decomposition analysis of the CI. Overall, the positive CI from the results indicates that the burden of obesity is more concentrated among the rich compared to the poor with girls having slightly greater SE inequalities compared to boys. The decomposition analysis further indicated that the determinants of these inequalities were an interplay of individual (i.e. race), household (i.e. household head characteristics) and contextual (i.e. household location) level factors. These findings suggest that there is a continuous need for surveillance of obesity in children over time across different social economic status (SES) especially in low- and middle- income countries. Finally, the results suggest that both childhood obesity and inequalities are complex issues with different underlying determinants that vary with the different SES, gender and may require coordinated policy and programmatic interventions at individual, household and contextual level.